STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN KEPULAUAN ANAMBAS - Hakim, Mukhtar; Sarma, Mamun; Harianto, Harianto (Jurnal Manajemen Pembangunan Daerah, 2018)
ABSTRACTRealization of Local Revenue (PAD) Anambas Islands Regency fluctuates through years, even tends to decline. The main problems faced in achieving the PAD target are due to (1) exploration of potential sources of regional income which is not optimal; (2) limitation of good quality of government’servant resources; (3) working culture of the servant in carrying out public services which is not optimal yet; (4) inadequate supporting facilities and infrastructures; (5) development of information systems in local financial management which is not optimal. The general objective of this research was to formulate strategies to increase PAD in Anambas Islands Regency. The study was conducted in Anambas Islands District on divisons and agencies which directly related to PAD. Primary data were obtained from direct interview, while secondary data were obtained from reports and documents from various related agencies. Data were analyzed by analysis of effectiveness ratio, efficiency ratio and regional independence ratio. The results of this study are (1) the effectiveness of regional income of Anambas Islands Regency during 2011-2015 fluctuated and the efficiency of PAD in Anambas Islands Regency tended to increase, (2) The ratio of regional independence was still low, (3) The main strategy implemented in the Anambas Islands Regency in order to increase PAD was an improvement in the management of regional income by optimizing the potential of PAD.Keyword    : Local Revenue  (PAD), Effectiveness, Efficiency, Independence, Strategy to Increase ABSTRAKRealisasi PAD Kabupaten Kepulauan Anambas dari tahun ke tahun mengalami fluktuasi, bahkan cendrung mengalami penurunan. Permasalahan utama yang dihadapi dalam mencapai target PAD disebabkan oleh (1) Belum optimalnya penggalian potensi sumber-sumber penerimaan daerah; (2) Masih terbatasnya Sumberdaya Aparatur Pemerintah yang berkualitas; (3) Belum optimalnya budaya kerja aparatur dalam melaksanakan pelayanan publik; (4) Sarana dan Prasarana penunjang yang kurang memadai; (5) Belum optimalnya pengembangan sistem informasi dalam pengelolaaan keuangan daerah.  Tujuan umum dari penelitian ini adalah untuk merumuskan strategi peningkatan PAD di Kabupaten Kepulauan Anambas. Tempat kajian dilakukan di Kabupaten Kepulauan Anambas pada Dinas dan instansi yang berkaitan langsung dengan PAD. Data primer diperoleh dari wawancara langsung, sedangkan data sekunder diperoleh dari laporan dan dokumen yang didapat dari berbagai instansi terkait. Data dianalisis dengan analisis rasio efekivitas, rasio efisiensi dan rasio kemandirian daerah. Hasil yang didapat dari kajian ini (1) Efektivitas PAD Kabupaten Kepulauan Anambas selama tahun 2011-2015 berfluktuasi dan efisiensi PAD Kabupaten Kepulauan Anambas cenderung membaik, (2) Rasio kemandirian daerah masih rendah, (3) Strategi prioritas utama yang di terapkan di Kabupaten Kepulauan Anambas untuk meningkatkan PAD adalah peningkatan dalam pengelolaan pendapatan daerah dengan mengoptimalkan potensi PADKata kunci : Pendapatan Asli Daerah (PAD), Efektivitas, Efisiensi, Kemandirian, Strategi Peningkatan